Yiddish periodicals published by displaced persons, 1946-1949 - Kuper Margalioth, A (1997)
This thesis is intended to demonstrate the existence of a vibrant cultural and literary life among the survivors of the Holocaust during their time as Displaced Persons (DPs) in Germany, Austria and Italy. It delineates their historical background, presents theoretical problems with which they may have been confronted, and explains the lack of previous academic research into their creative production. It then analyzes three representative literary journals from the period 1946 to 1949, when the DP population was at its peak: In Gang: khoydesh-zhurnal far literatur un kunst / khoydesh-zhurnal far literatur, kultur un gezelshaftlekhe problemen (In Progress: Monthly Journal of Literature and Art / Monthly Journal of Literature, Culture and Societal Problems), published in Rome between March 1947 and February 1949; Fun letstn khurbn: tsaytshrift far geshikhte fun yidishn lebn beysn natsi-rezhim (From the Last Extermination: Journal for the History of the Jewish People During the Nazi Regime), published in Munich between August 1946 and December 1948; and Shriftn far literatur, kunst un gezelshaftlekhe fragn (Writings for Literature, Art and Societal Questions), published in Kassel, Germany in January 1948. These journals were chosen because their editorial material reflected strong commitments to dealing with the political and especially the cultural issues of the day. These included the on-going examination of the possibility of Jewish cultural continuity, the drive for a Jewish state, and the attempt to come to terms with the immensity and horrors of the Holocaust. The thesis also includes an annotated bibliography of the contents of these three journals which is intended to improve their accessibility for future study.